Status of Property Assets in Marriages Without a Prenuptial Agreement from the Perspective of the Civil Code and the Marriage Law: A Review of Supreme Court Decision No. 2981 K/Pdt/2024 - Jessica Leticia; Mia Hadiati (Academia Open, 2025)
General background: The regulation of property assets in Indonesian marriage law operates within a dual framework involving the Civil Code and the Marriage Law, each establishing different principles on ownership and control. Specific background: These differences create practical ambiguity in marriages concluded without a prenuptial agreement, particularly when determining the status of separate and marital property upon dissolution. Knowledge gap: Despite substantial jurisprudence, limited scholarly analysis examines how both legal regimes interact in real disputes, especially in cases where property acquired before marriage becomes contested inheritance. Aims: This study analyzes the status and distribution of property assets in marriages without a prenuptial agreement by comparing the Civil Code and the Marriage Law, using Supreme Court Decision No. 2981 K/Pdt/2024 as a case reference. Results: The findings show that during marriage, property classification follows the Marriage Law, but upon dissolution—especially by death—the distribution of assets reverts to the parties’ respective legal system, resulting in the Civil Code governing inheritance for those subject to civil law. Novelty: This research clarifies the normative intersection between marital property and inheritance law in the absence of prenuptial agreements. Implications: The study highlights the need for harmonization between the Marriage Law and the Civil Code to ensure legal certainty and prevent interpretive inconsistencies in future marital property disputes. Highlights: Clarifies differences between the Marriage Law and the Civil Code in regulating property without a prenuptial agreement. Highlights how dissolution of marriage shifts asset distribution to the parties’ applicable legal system. Emphasizes the need for harmonization to prevent inconsistent judicial interpretations. Keywords: Marital Property, Separate Property, Civil Code, Marriage Law, Inheritance